Musadoc 2001: CD-Rom - International Network for the Improvement of Banana and Plantain (2001)
The up-to-date versions of the INIBAP databases, MUSALIT - containing abstracts and bibliographic records of publications on Musa, and BRIS - the database of banana researchers are available. As are all of the recent publications, including the popular Banana brochure, new factsheets and publications from 2001, such as the 2000 Annual Report.